WOMAN IN THE GREY AREA' DALAM FILSAFAT DISCOURSE: MANUSIA, PEREMPUAN DAN SEKS WORKER - Suharnanik, Suharnanik (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Humans as a single unified whole that unites between soul and body. Homan reputed to exist if that organism is reputed exist, it means meaning full that determine human acknowledged. The sex of human organism is male or female even gray areas are determined based on objectivity and subjectivity that inherent in visible or not visible. In the word of